2021
DOI: 10.1002/2211-5463.13331
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and metabolomic analysis of Nicotiana benthamiana under dark stress

Abstract: Exposure to extended periods of darkness is a common source of abiotic stress that significantly affects plant growth and development. To understand how Nicotiana benthamiana responds to dark stress, the proteomes and metabolomes of leaves treated with darkness were studied. In total, 5763 proteins and 165 primary metabolites were identified following dark treatment. Additionally, the expression of autophagy-related gene (ATG) proteins was transiently upregulated. Weighted gene coexpression network analysis (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 98 publications
(117 reference statements)
0
2
0
Order By: Relevance
“…Interestingly, previous studies have reported that RPSaA, RPS5A, and RPS24A have roles in the regulation of reactive oxygen species (ROS)-mediated systemic signaling. RPS5A may play an important role in dark treatment by participating in the autophagy regulatory process, which is triggered to degrade excessive ROS to help protect cells [90]. Then, it was shown that RPSaA and RPS24A had lower degradation rates and were more stable after oxidative stress [91].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, previous studies have reported that RPSaA, RPS5A, and RPS24A have roles in the regulation of reactive oxygen species (ROS)-mediated systemic signaling. RPS5A may play an important role in dark treatment by participating in the autophagy regulatory process, which is triggered to degrade excessive ROS to help protect cells [90]. Then, it was shown that RPSaA and RPS24A had lower degradation rates and were more stable after oxidative stress [91].…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, RPS27B has been said to act as a regulator of transcript stability in response to genotoxic treatments via the degradation of damaged RNAs [39]. Recent data have shown that mutations in RPS27B influence the integrity of ribosomes in both structure and function [90].…”
Section: Discussionmentioning
confidence: 99%